Competence-Based Trust in Token-Based New Ventures - Jorge, João Maria; Fassio, Claudio; Mattsson, Pauline (Academy of Management Proceedings, 2025)
This paper investigates the importance of competence-based trust on the fundraising success of Initial Coin Offerings. Based on a dataset with 3,644 ICOs, our models test the influence of generic and specific human capital on the probability of token-based new ventures to secure the amount of funds they intended to during ICOs. Our results suggest a positive and statistically significant influence of the previous working experience (generic human capital) of the whole TMT. Additionally, our results also point to the importance of college education (generic human capital) of the CEO for prospective investors, whereas in the case of the CTO both generic human capital and specific human capital (associated to knowledge about crypto and blockchain) are important screening mechanisms used by prospective investors to assess the quality of token-based new ventures.